Tax justice as means of achieving social justice: Case study of Algeria - Kechitti, hocine (Journal of Research in Finance and Accounting, 2021)
The present research analyses the role of tax system in the equitable distribution of tax burden and thus the optimal distribution of income (wealth), which will contribute to achieve social justice. The study explores the nature of tax justice, its types, the means to help achieve it, and its relationship with social justice. We tried to focus on tax system in Algeria, its characteristics and components, and the reforms that affected its various aspects to build a more just distribution of the tax burden as well as taking into account the social aspect when granting various privileges and tax exemptions. We have come to the conclusion that the tax system in Algeria still suffering many problems reducing its fairness and effectiveness. This is noteworthy in view of high tax rates, weak tax revenues, and the spread of tax evasion.